Formulation of Gel Extract of Gamat Leaf (Tinomiscium Petiolare Hook.F & Thomson) in Healing of Diabetic Ulcers and Bacterial Inhibitory Power in Rats - Mawaqit Makani; Iqlila Romaidha; Olinda Kaulika (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetic foot ulcers (DFUs) present a critical clinical challenge, where persistent bacterial infections frequently stall the healing cascade and escalate amputation risks. This delayed recovery is worsened by growing antibiotic resistance against conventional topical agents, underlining an urgent demand for multi target, plant derived alternatives. Although Tinomiscium petiolare Hook.f. & Thomson (locally known as Gamat leaf) is rich in tissue regenerative and antimicrobial compounds, its therapeutic potential in chronic diabetic wound microenvironments has not yet been investigated. This study aimed to formulate Gamat leaf extract (Tinomiscium petiolare) into a gel preparation and evaluate its effectiveness on diabetic ulcer healing and antibacterial inhibitory power in vivo using diabetic rat models. Method: This experimental study included the extraction of Gamat leaves by maceration with 96% ethanol, followed by gel formulation with varying extract concentrations (F1, F2, F3). The bacterial inhibition test was conducted in vitro (well method). The in vivo test used male Wistar rats induced by streptozotocin (STZ) to achieve a diabetic condition, then an excision wound was made as an ulcer model. The parameters observed included physical evaluation of the gel, percentage of wound area shrinkage over 14 days, and bacterial inhibition zone. GC-MS analysis identified dominant bioactive compounds with anti-inflammatory and antioxidant properties. The preparation showed stable viscosity, ensuring optimal adhesion and active ingredient penetration. HE results demonstrated significant increases in collagen deposition and epithelialization compared to the control group. The synergy of chemical, physical, and biological parameters proves that Gamat Leaf is a strong candidate for standardized pharmaceutical ingredients in accelerating wound healing.